Xanthostemon novoguineensis: An Ethnobotany Perspective Towards Conservation of Endemic Species and Potentials for Renewable Energy (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
There is increasing interest in conserving plant endemics because they face a high risk of extinction in their natural habitats and support traditional functions for local communities. This perspective review paper aims to provide a view of the future of the ethnobotany of Xanthostemon novoguineensis, which can be used to conserve this plant in the forests of Papua Province, Indonesia. Thus, it is presented as a personal view on critical thinking about future challenges to protecting this plant. First, the history of this plant is described, from its invention in Papua New Guinea. Subsequently, a discussion of the ethnobotanical perspective on the conservation of X. novoguineensis, based on a recent literature review, is provided. The final section discusses the near-future challenge associated with X. novoguineensis and how the ethnobotanical perspective of Papuans, especially the Sentani tribes, may hold vital value for the sustainability of X. novoguineensis.
Keywords: Conservation; Ethnobotany; Renewable Energy Resources; X. novoguinensis